Internet Financial Report And Determinants of The Quality of Financial Statements of Non-Profit Organizations - Hardiyanto, Nico; Ahmar, Nurmala; Etty Merawati, Endang (Devotion : Journal of Research and Community Service, 2023)
The purpose of this research was to assess the elements that influence the quality of non-profit financial statements and the moderation of voluntary disclosures on the Internet Financial Report. " Human Resource Competence, Implementation of Financial Accounting Standards for Non-Profit Organizations, Internal Control Systems, and Accounting Information Technology Use on the Quality of Financial Reports of Non-Profit Organizations with Voluntary Disclosure of Internet Financial Reports as Moderating Variables,". The population in this research is all non-profit organizations in the form of NGOs or NGOs in Indonesia. The research sample is focused on NGOs and NGOs registered with the Ministry of Foreign Affairs until 2021, as well as partners from donor agencies USAID and AUSAID. The primary data sampling technique was convenience sampling, where respondents who were willing to fill out the questionnaire were sampled. Distribution of online questionnaires and surveys through private domains obtained 90 respondents from the financial staff of non-profit organizations that were willing to participate in this research. The data was processed using a multiple linear regression analysis. The results of this research indicate that the influence of human resource competence, the implementation of financial accounting systems for non-profit organizations, the implementation of internal control systems, and the utilization of accounting information technology affect the quality of financial reports of non-profit organizations, while voluntary disclosure of internet financial reports strengthens the relationship between the utilization of accounting information technology and report quality. Finance for nonprofit organizations.